Manajemen Pelayanan Kesehatan Berbasis Pesantren Melalui Santri Husada - Zainal Abidin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Health services at Islamic boarding schools are a must because Islamic boarding schools are a gathering place for many children who are studying. The existence of Islamic boarding schools is a national asset, so they must be protected for the sake of the nation's progress. Health problems suffered by students will disrupt their worship and study activities. This article will review Islamic boarding school-based health service management. This research uses a natural approach, namely quantitative. Data collection was carried out using in-depth interview techniques, participant observation, and documentation. After the data is collected, the next step is to carry out condensation or compaction so that pearls of data are found, which are very important in this research. Next is the display and verification process. In order for the results of this research to be credible, an analysis of the validity of the data was carried out by carrying out triangulation, either data triangulation or source triangulation. Apart from that, researchers also conducted member checks and discussions with colleagues. The results of this research show that the existence of Husada students in the Islamic boarding school environment is as an internal health service, as an agent for health education, helping other students who are sick, providing opportunities for Husada students to develop health skills, and integrating religious knowledge with health in Islamic boarding schools.